Post‐MI treatment with G‐CSF and EPO‐liposome with SLX repairs infarcted myocardium through EPCs mobilization and activation of prosurvival signals in rabbits. Issue 1 (21st December 2018) - Yamada, Yoshihisa; Minatoguchi, Shingo; Endo, Noriko; Kanamori, Hiromitsu; Kawasaki, Masanori; Nishigaki, Kazuhiko; Mikami, Atsushi; Minatoguchi, Shinya
Abstract: We investigated whether combination therapy of G‐CSF and erythropoietin (EPO)‐liposome with Siaryl Lewis X (SLX) is more cardioprotective than G‐CSF or EPO‐liposome with SLX alone. For the purpose of generating myocardial infarction (MI), rabbits underwent 30 minutes of coronary occlusion and 14 days of reperfusion. We administered saline (control group, i.v., ), G‐CSF (G group, 10 μg/kg/day × 5 days, i.c., starting at 24 hours after reperfusion), EPO‐liposome with SLX (LE group, i.v., 2500 IU/kg EPO containing liposome with SLX, immediately after reperfusion), and G‐CSF + EPO‐liposome with SLX (LE + G group) to the rabbits. The MI size was the smallest in the LE+G group (14.7 ± 0.8%), and smaller in the G group (22.4 ± 1.5%) and LE group (18.5 ± 1.1%) than in the control group (27.8 ± 1.5%). Compared with the control group, the cardiac function and remodeling of the G, LE, and LE + G groups were improved, and LE + G group tended to show the best improvement. The number of CD31‐positive microvessels was the greatest in the LE + G group, greater in the G and LE groups than in the control group. Higher expressions of phosphorylated (p)‐Akt and p‐ERK were observed in the ischemic area of the LE and LE + G groups. The number of CD34 + /CXCR4 + cells was significantly higher in the G and LE + G groups. The cardiac SDF‐1 was more expressed in the G and LE + G groups. In conclusion, Post‐MI combination therapy with G‐CSF and EPO‐liposome with SLX is more cardioprotective than G‐CSF or EPO‐liposome with SLX alone through EPCs mobilization, neovascularization, and activation of prosurvival signals.